How diverse is Mitopus morio? Integrative taxonomy detects cryptic species in a small‐scale sample of a widespread harvestman. Issue 14 (4th June 2013) - Arthofer, Wolfgang; Rauch, Hannes; Thaler‐Knoflach, Barbara; Moder, Karl; Muster, Christoph; Schlick‐Steiner, Birgit C.; Steiner, Florian M.
Abstract Mitopus morio is a widespread harvestman species occurring in most of Europe and in moderate and cold‐moderate zones of Asia and North America. The species is characterized by extreme variability in body size and leg length. As leg length is correlated with habitat temperature, M. morio has been considered as an example of Allen's rule. Recently, observations for a single location in Tyrol, Austria, indicated the absence of mating between short‐ and long‐legged individuals. This study examines for signs of putative cryptic species in M. morio using an integrative approach that combines mating trials, amplified fragment length polymorphism whole‐genome scans, mitochondrial sequences and morphometrics. The mating trials did not corroborate the initial hypothesis of a reproductive barrier associated with leg size. Both types of genetic data revealed the existence of three distinct groups, in line with the mating results but largely unrelated to leg morphology and geographical origin of specimens. Morphometric characters supporting the findings of the other disciplines were identified using a supervised approach. We infer from all data together the existence of strongly diverged cryptic lineages among the analysed individuals, cautiously interpret them as three sympatric species and conclude that in these harvestmen Allen's rule applies at different levels. Due to the unexpected amount of differentiation found within a geographical scale very small compared with the distribution of M. morio, we suggest a thorough revision of the genus prior to formal taxonomic changes. Our case study underlines the general applicability of the integrative taxonomic protocol used and highlights the relevance of several rationales implemented in the protocol.